Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1152/ajpheart.01123.2010
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of coronary microvascular resistance using angiographic images for volumetric blood flow measurement: in vivo validation

Abstract: Zhang Z, Takarada S, Molloi S. Quantification of coronary microvascular resistance using angiographic images for volumetric blood flow measurement: in vivo validation. Am J Physiol Heart Circ Physiol 300: H2096 -H2104, 2011. First published March 11, 2011 doi:10.1152/ajpheart.01123.2010.-Structural coronary microcirculation abnormalities are important prognostic determinants in clinical settings. However, an assessment of microvascular resistance (MR) requires a velocity wire. A first-pass distribution analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The angiographic CFR and FFR methods, which require no wire, reduce the cost and procedure time compared with the other techniques. All procedures can be completed during a routine diagnostic cardiac catheterization (46). The arterial lumen volume can be used to 1) predict the expected maximum blood flow in an arterial tree (21,26), and 2) normalize the maximum hyperemic blood flow for different size arteries (46,47).…”
Section: Advantages Of the Angiographic Measurement Based On Fpamentioning
confidence: 99%
“…The angiographic CFR and FFR methods, which require no wire, reduce the cost and procedure time compared with the other techniques. All procedures can be completed during a routine diagnostic cardiac catheterization (46). The arterial lumen volume can be used to 1) predict the expected maximum blood flow in an arterial tree (21,26), and 2) normalize the maximum hyperemic blood flow for different size arteries (46,47).…”
Section: Advantages Of the Angiographic Measurement Based On Fpamentioning
confidence: 99%
“…1). Our laboratory's previous report has validated that the angiographic flow based on the FPA technique (Q a) has strong correlations with flow from the flow probe in the swine microvascular disruption model (43).…”
Section: Methodsmentioning
confidence: 82%
“…FPA technique, using angiographic image data, has previously been used to measure absolute coronary blood flow through a stenotic artery (26,27). Our laboratory's previous report (43) focused on validation of the FPA technique in a swine microvascular disruption model. It showed that angiographic NMR measurement based on the FPA technique has good accuracy and reproducibility.…”
Section: H404 Assessment Of Coronary Microcirculation In a Swine Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiographic FFR technique, which includes the effects of both epicardial and microvascular disease, can be used to assess coronary flow reserve (14), microvascular resistance (13,15), as well as FFR to provide a detailed diagnosis for the entire coronary arterial system.…”
mentioning
confidence: 99%